Facilitating Access to Prenatal Care Through an Interprofessional Student‐Run Free Clinic. (24th March 2015) - Danhausen, Kathleen; Joshi, Deepa; Quirk, Sarah; Miller, Robert; Fowler, Michael; Schorn, Mavis N.
Abstract : Introduction: Addressing the persistent challenge of inadequate prenatal care requires innovative solutions. Student‐run free health centers are poised to rise to this challenge. The Shade Tree Clinic Early Pregnancy Program, jointly operated by university medical and nursing programs, functions as an ongoing access‐to‐care portal for pregnant women without health insurance. The clinic is run by medical students and nurse‐midwifery students and uses a service‐based learning model that allows students to work and learn in supervised, interprofessional teams while providing evidence‐based prenatal care. Methods: All data reported in this paper were obtained from a retrospective chart review of women served by the prenatal clinic. These data are descriptive in nature, and include the patient demographics and services provided by the clinic to 152 women between the years of 2010–2013. Results: During this time period, the clinic served a demographically diverse clientele. Approximately half lacked documentation of legal immigration status. The majority of women seeking care were in their first trimester of pregnancy and had previously given birth. Several women had medical or obstetric complications that required timely referral to specialist care; and many women received treatment for infection and other primary care concerns. Discussion: Shade Tree Clinic provides the basic components of prenatal care and assists women with other medical needs. Women also receive help when applying for and accessing public maternity insurance, and the clinic facilitates entry to any necessary specialist care while that insurance is processed. In many cases, necessary and time‐sensitive care would be delayed if Shade Tree Clinic's prenatal services were not available. In addition, the clinic presents a valuable opportunity for interprofessional socialization, increased respect, and improved collaboration between students in different but complementary professions, which is an important experience while we move to meet national goals for interprofessional care among health professionals. This article is part of a special series of articles that address midwifery innovations in clinical practice, education, interprofessional collaboration, health policy, and global health.